2022
DOI: 10.3390/jcm12010207
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Patients Treated with JAK Inhibitors in Rheumatoid Arthritis before versus after VTE Risk Warnings

Abstract: Background: Baricitinib (BARI) or Tofacitinib (TOFA) were the first Janus Kinase Inhibitors (JAKi) to be marketed in rheumatoid arthritis (RA). Concerns regarding venous thromboembolism (VTE) risk have emerged during the past years. The aim of the study was to compare the baseline characteristics of patients initiating BARI or TOFA in RA before versus after European Medicine Agency (EMA)’s VTE warnings and to compare real-world persistence with these two drugs. Methods: In this multicentric cohort study, RA pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Concerning serious adverse events, McInnes et al (2021) and Reich et al (2022) reported the higher incidences of serious adverse events in patients receiving upadacitinib (30-mg dose) and adalimumab, respectively. According to European Medicine Agency (EMA) and US Food and Drug Administration (FDA) recent warnings, JAKi were associated with increased risks of major adverse cardiac events, cancer, venous thromboembolic events, severe infections, and death ( Kragstrup et al, 2022 ; Philippoteaux et al, 2022 ), and clinicians needs to carefully consider risk factors and assess corresponding risks of individual patients before use of JAKi. For the arthritis activity endpoint, skin endpoint, and drug retention, qualitative descriptions were provided since unsynthesizable data from the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning serious adverse events, McInnes et al (2021) and Reich et al (2022) reported the higher incidences of serious adverse events in patients receiving upadacitinib (30-mg dose) and adalimumab, respectively. According to European Medicine Agency (EMA) and US Food and Drug Administration (FDA) recent warnings, JAKi were associated with increased risks of major adverse cardiac events, cancer, venous thromboembolic events, severe infections, and death ( Kragstrup et al, 2022 ; Philippoteaux et al, 2022 ), and clinicians needs to carefully consider risk factors and assess corresponding risks of individual patients before use of JAKi. For the arthritis activity endpoint, skin endpoint, and drug retention, qualitative descriptions were provided since unsynthesizable data from the included studies.…”
Section: Discussionmentioning
confidence: 99%
“…The Food and Drug Administration (FDA) labels for tofacitinib, upadacitinib, and abrocitinib indicate a higher frequency of serious infections especially in older adults, the FDA label for baricitinib states that no overall differences in the safety and efficacy of the drug were observed between older and younger adults. FDA labels for abrocitinib and upadacitinib also indicate a higher frequency of malignancy in elderly patients, and an increased risk of major cardiovascular events, and thrombosis in patients with rheumatoid arthritis ( 36 , 37 ). Based on data from the use of tofacitinib on rheumatoid arthritis, the European Medicines Agency (EMA) has recently raised concerns about the use of JAK inhibitors in patients older than 65 years and recommended caution in their use only when no suitable alternative treatment options are available ( 38 ).…”
Section: Treatment Of Atopic Dermatitis In the Elderly Populationmentioning
confidence: 99%
“…The overall risk of VTE with vedolizumab is low[ 91 , 92 ]. Pooled safety analysis from Phase 2/3 studies on ustekinumab reported no significant difference in VTE risk in patients treated with ustekinumab compared to placebo (0.75/100 person years vs 0.34/100 person years, respectively)[ 93 - 95 ].…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 99%
“…Janus kinase (JAK) inhibitors: A safety study done in patients older than 50 year with rheumatoid arthritis and more than one cardiovascular risk factor showed that VTE, DVT and PE was higher for tofacitinib when used in the dose of 10 mg twice daily[ 95 ]. Similar to these observations, in the OCTAVE open study, with a follow-up of 7 years, 10 mg tofacitinib group had 0.1% and 0.7% prevalence of DVT and PE, respectively [IR = 0.06 (95%CI: 0.00-0.31) and 0.28 (95%CI: 0.09-0.65)].…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 99%